Kesetaraan Gender Pada Film Tiongkok Mulan - Masruroh, Annis; Farhan Masrur, Muhammad (Universitas Pakuan, 2025)
GENDER EQUALITY IN CHINESE FILM MULANThis study aims to analyze the representation of gender equality in the Chinese film Mulan using a qualitative approach through the Systematic Literature Review (SLR) method. The research is grounded in the issue of gender inequality that remains prevalent in China’s patriarchal culture, where women are often placed in subordinate positions and viewed as lacking the same capacities as men. Mulan serves as a compelling case, portraying a female character who defies social systems, fights on the battlefield, and proves that courage and intelligence are not limited by gender. The literature review draws on previous studies relevant to feminism and female representation in media. The findings reveal that Mulan represents gender equality through four main dimensions: access, participation, control, and benefit. The character Mulan is depicted as an independent and courageous woman who possesses existential awareness to determine her own destiny. These results reinforce Simone de Beauvoir’s existentialist feminist view that women can be subjects who are free and responsible for their existence. Therefore, Mulan is not merely a heroic tale but also an ideological manifestation of women’s struggle to uphold gender equality within a patriarchal culture.